Respuesta :

Answer:

(-1, 0)

I will solve your system by substitution.

(You can also solve this system by elimination.)

2x+y=−2;−3x+2y=3

Step: Solve2x+y=−2for y:

2x+y+−2x=−2+−2x(Add -2x to both sides)

y=−2x−2

Step: Substitute−2x−2foryin−3x+2y=3:

−3x+2y=3

−3x+2(−2x−2)=3

−7x−4=3(Simplify both sides of the equation)

−7x−4+4=3+4(Add 4 to both sides)

−7x=7

−7x

−7

=

7

−7

(Divide both sides by -7)

x=−1

Step: Substitute−1forxiny=−2x−2:

y=−2x−2

y=(−2)(−1)−2

y=0(Simplify both sides of the equation)